Low frequency of cytomegalovirus (CMV) disease despite high prevalence of CMV viraemia in patients with advanced HIV infection: a clinical and immunological 48‐week follow‐up study. Issue 8 (17th May 2021) - Albasanz‐Puig, A; Suanzes, P; Esperalba, J; Fernández, C; Sellarès‐Nadal, J; Torrella, A; Planas, B; Segura, A; Burgos, J; Ribera, E; Cañas‐Ruano, E; García, JN; et al.
Abstract : Objectives: The aim of the study was to investigate the dynamics of cytomegalovirus (CMV) replication and CMV‐specific immune response recovery after antiretroviral treatment (ART) initiation in patients with advanced HIV infection. Methods: A prospective observational study of patients with HIV infection and CD4 counts of < 100 cells/µL was carried out (September 2015 to July 2018). HIV viral load (VL), CD4 count and CMV VL were determined by quantitative polymerase chain reaction (PCR) at baseline and at 4, 12, 24 and 48 weeks, and CMV‐specific immune response was determined by QuantiFERON‐CMV assay at baseline and 48 weeks. All patients were started on ART but only those with CMV end‐organ disease (EOD) received anti‐CMV treatment. Results: Fifty‐three patients with a median age of 43.6 [interquartile range (IQR) 36.7–52.4] years were included in the study. At baseline, the median CD4 count was 30 cells/µL (IQR 20–60 cells/µL) and the median HIV VL was 462 000 HIV‐1 RNA copies/mL (IQR 186 000–1 300 000 copies/mL). At baseline, 32% patients had detectable CMV viraemia but none had detectable CMV viraemia at 48 weeks. Only one of 53 (1.9%) patients developed EOD during follow‐up. Seven (13.2%) patients were lost to follow‐up and six (11.3%) died; none of the deaths was related to CMV. Similar percentages of patients had a CMV‐specific immune response at baseline (71.7%) and at 48 weeks (70.0%). The magnitude of this response tended to increase over time [median 1.63 (IQR 0.15–5.77) IU/mL at baseline vs . median 2.5 (IQR 0.1–8.325) IU/mL at 48 weeks; P  = 0.11]. We did not find any risk factors associated with 48‐week mortality. Conclusions: Although the prevalence of CMV viraemia in patients with advanced HIV infection remains high, achieving a good immunological recovery through ART is enough to suppress CMV viraemia, without an increased risk of CMV EOD. The prevalence of a CMV‐specific immune response was high and endured over time.